Konstruksi Makna Peran Suami yang Tidak Bekerja dalam Keluarga di Rengasdengklok Kabupaten Karawang - Siti Nazarina Rahma (Lembaga Pengembangan Kinerja Dosen, 2025)
The phenomenon of unemployed husbands in Rengasdengklok, Karawang Regency, reflects a shift in family roles influenced by economic, health, and educational factors. In the context of patriarchal culture, husbands typically serve as the primary breadwinners; however, many are now taking on domestic responsibilities while their wives work as Overseas Female Workers (TKW). This study employs a qualitative approach with a phenomenological method to understand the experiences and meanings constructed by unemployed husbands. The findings indicate that unemployed husbands often experience psychological pressure and social stigma, while their wives become the family's primary providers. Intrapersonal and interpersonal communication play crucial roles in shaping self-acceptance and maintaining family harmony amid existing challenges. This research highlights the complexity of family dynamics and the role changes that occur due to socio-economic conditions